A comprehensive insight into effects of green tea extract in polycystic ovary syndrome: a systematic review - Vahid Maleki; Ehsaneh Taheri; Parisa Varshosaz; Fatemeh Pourteymour Fard Tabrizi; Jalal Moludi; Hamed Jafari-Vayghan; Mahdi Shadnoush; Seyed Hossein Yahyazadeh Jabbari; Mehri Seifoleslami; Mohammad Alizadeh (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS), as the most common endocrine disorder in reproductive-aged women, is characterized by oxidative stress and ovarian tissue inflammation. Green tea extract (GTE) potentially possesses therapeutic effects for PCOS because of the antioxidant and anti-inflammatory compounds. This systematic review evaluates the potential roles of GTE on metabolic variables, hormone levels, and ovarian function in PCOS. Methods A systematic review was conducted of published studies reporting the effects of GTE on PCOS. Several major databases, including PubMed, SCOPUS, and Google Scholar, were searched up from inception to April 2021. Clinical trials and animal studies that assessed the effects of GTE on PCOS were eligible for inclusion. Results Of 314 articles found in the search, four human studies and four animal studies were included. All studies in humans showed the effects of GTE on weight loss. GTE's effect on decreasing testosterone levels in humans and LH levels in animals were also reported. In addition, increases in FSH and progesterone levels in animal models were observed. Although GTE improved fasting blood sugar and insulin levels, the effect of GTE on inflammatory parameters, such as TNF-alpha and IL-6 and antioxidant status, was limited to animal studies. Conclusion Therefore, this review suggests that GTE could be considered a potential agent to attenuate PCOS complications mainly due to its effect on weight loss and glycemic levels. However, more studies are needed to formulate conclusions about the effects and mechanisms of GTE in PCOS.